Providensi Ilahi dan Harapan Manusia: Interpretasi Pemilihan Daud sebagai Raja dalam 1 Samuel 16:1-13 - Laoly, Nepho Gerson (Institut Agama Kristen Negeri Tarutung, 2024)
This research examines the theological significance of God’s Choice of David as king in 1 Samuel 16:1-13 and analyzes the relationship between divine providence and human expectation in this passage. It argues that God’s choice of David as king was not solely a matter of divine providence, but also a response to human expectations. Through literary and textual analysis, historical and cultural contextualization, and critical evaluation of existing scholarship, the research highlights themes such as the rejection of Saul, the significance of the anointing oil, and the importance of David character and upbringing. This research aims to contribute to the fields of biblical studies and theology by offering a nuanced interpretation of God’s choice of David as king in 1 Samuel 16:1-13 that considers both divine and human agency, and its broader implications for understanding God’s role in history. AbstrakPenelitian menelaah signifikansi teologis Pemilihan Tuhan atas Daud sebagai raja dan menganalisis keterkaitan providensi ilahi dan harapan manusia pada bagian ini. Pilihan Tuhan atas Daud sebagai raja bukan hanya masalah providensi ilahi, namun juga respons atas harapan manusia. Melalui analisis sastra teks, kontekstualisasi sejarah budaya, serta evaluasi kritis riset yang ada, penelitian menyoroti tema penolakan terhadap Saul, minyak pengurapan, karakter dan latar belakang Daud. Penelitian memberikan interpretasi mendalam Pemilihan Tuhan atas Daud sebagai raja di 1 Samuel 16:1-13 , mempertimbangkan pengaruh ilahi dan manusia, implikasi luas untuk memahami Tuhan dalam sejarah, sehingga memberikan kontribusi pada studi Alkitab dan teologi.